Pengaruh Penggunaan Akun Instagram @pelangibundamedika terhadap Pemenuhan Informasi Pasien Klinik Pelangi Klinik Pelangi Bunda Medika - Dewi Ilma Agustin; Noerma Kurnia Fajarwati; Meiby Zulfikar; Rizqi Fitrianti; Arfian Suryasuciramdhan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to determine the influence of @pelangibundamedika Instagram account on the fulfillment of patient information needs at the Rainbow Bunda Medika Clinic. Using the theory of Uses and Gratifications as a foundation, this study examines how patients actively use social media to obtain health information, such as doctor's practice schedules, educational materials, and service promotions. The method used was quantitative associative with a survey approach of 100 respondents. Data were collected through a structured questionnaire and analyzed using validity, reliability, as well as simple linear regression tests with the help of SPSS software. The results of the analysis showed that the use of Instagram had a positive and significant influence on the fulfillment of patient information needs, with a determination coefficient value of 46.8%. These findings indicate that almost half of patients' information needs are met through the clinic's Instagram account, while the rest are influenced by other factors such as in-person consultations, verbal communication, or alternative media. The conclusion of this study is that Instagram is an effective medium in conveying health information that is relevant, easily accessible, and timely. The practical implications of the results of this study are the need to optimize Instagram's content strategy, including improving visual quality, consistency of upload schedules, and interactivity with followers. In addition, the use of other digital platforms is also recommended to expand the reach of information and increase patient trust and satisfaction with clinic services.